Identification, semi-quantification, and dynamics of volatile organic compounds during spontaneous fermentation of two cocoa varieties from northern Peru, using HS-SPME/GC-MS techniques: - CRUZ-ROJAS, Lorena Lizbeth; OLIVA-CRUZ, Segundo Manuel; RONDINEL-MENDOZA, Natalie Verónika; VILLEGAS-VILCHEZ, León Faustino; CAETANO, Aline Camila (Food Science and Technology, 2023)
During spontaneous fermentation, an important process through which cocoa beans pass, volatile organic compounds (VOCs) and non-VOCs are generated and act as precursors of aromas and flavors that influence the chocolate. In the north of Peru, cocoas of different varieties and qualities are grown, and one of the most valued is the fine aroma native cocoa (Cacao Fino de Aroma (CFA)) compared with the Castro Naranjal 51 Collection (CCN-51) variety. In this investigation, the VOCs generated during the spontaneous fermentation of CFA and CCN-51 varieties, from the department of Amazonas, Peru, were analyzed. For the extraction of VOCs, the headspace (HS) and solid-phase microextraction (SPME) techniques were used, while gas chromatography coupled to a mass spectrophotometer (GC-MS) was employed for their subsequent separation and identification. The spontaneous fermentation process lasted for 156 h, and a total of 122 VOCs were identified in 2 varieties. The dynamics of 20 VOCs were assessed, and the principal component analysis of 22 VOCs was performed to compare the profiles of VOC of the 2 cocoa varieties. In conclusion, the CFA variety presented higher concentrations of floral, fruity, and sweet aromatic VOCs that positively influence the quality of the chocolate.